Translation Strategy for Idioms in “The Schools For Good and Evil” - Ridwan, Nurhidayah; Putri, Astari Amalia (Huele: Journal of Applied Linguistics, Literature and Culture, 2025)
This study aims to analyze and explain the translation strategy of the idioms used in the film "The Schools for Good and Evil" by Soman Chainani. The basic problem in this study is the difficulty of translating the idioms in the film, therefore the right strategy is needed in its translation. The research method used is a descriptive qualitative method. A total of 14 idioms were found in the film and then became data in this study. The results of the study indicate that, based on four translation strategies of Baker's theory, there are14 idioms using 3 main theories; namely 1). 6 idioms use translation strategy of idioms with similar meaning and form; 2). 5 idioms use translation strategy of idioms with similar meaning but dissimilar form, and the last one, 3). 3 idioms use paraphrasing translation strategy. The frequent use of the similar meaning and form strategy shows that a lot of idioms in the film have direct equivalents in Indonesian, making translation straightforward.